2012
DOI: 10.1149/2.092206jes
|View full text |Cite
|
Sign up to set email alerts
|

One-Dimensional Phenomenological Model for Liquid Water Flooding in Cathode Gas Channel of a Polymer Electrolyte Fuel Cell

Abstract: The mathematical description of liquid water flooding in the gas channel (GC) of a polymer electrolyte fuel cell (PEFC) at the macro scale has remained a challenge up to now. The mist flow assumption in the GC has been commonly used in previous numerical studies. In this work, a one-dimensional (down-the-channel) macroscale phenomenological model for the liquid water flooding in the cathode GC is developed based on several reasonable assumptions. We focus on the operating conditions with fully humidified inlet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…That can be justified by the fact that high gas flow rates in the GC will remove emerging liquid water droplets effectively. Otherwise, water coverage effect [31,32] will be of concern which is beyond the scope of the present study. At the side boundaries, no-flux conditions are assumed.…”
Section: Boundary Conditionsmentioning
confidence: 95%
“…That can be justified by the fact that high gas flow rates in the GC will remove emerging liquid water droplets effectively. Otherwise, water coverage effect [31,32] will be of concern which is beyond the scope of the present study. At the side boundaries, no-flux conditions are assumed.…”
Section: Boundary Conditionsmentioning
confidence: 95%
“…The penetration model readily applies to the water drops in the flow field channel. 36 However, for the liquid water in the gas diffusion electrode, 37 the penetration model no longer applies as the gas velocity is significantly reduced within the solid porous structure with a pore characteristic dimension of the order of or less than 100 μm.…”
Section: -13mentioning
confidence: 99%
“…The penetration model readily applies to the water drops in the flow field channel. 36 However, for the liquid water in the gas diffusion electrode, 37 the penetration model no longer applies as the gas velocity is significantly reduced within the solid porous structure with a pore characteristic dimension of the order of or less than 100 μm.38 This difference significantly impact contaminant scavenging dynamics and it will be shown that the product liquid water in a PEMFC is always saturated by the contaminant greatly simplifying analysis.A model is proposed for the water scavenging effect inside PEMFCs. A time scale analysis of the different processes within the PEMFC revealed that the contaminant saturates water droplets in the gas diffusion electrode.…”
mentioning
confidence: 99%
“…A phenomenological model 36 accounted for droplet and corner film conditions in channels with momentum exchange with the air but did not track the droplets explicitly. In another study, 37 the gas channel was coupled to a MEA where droplet dynamics were simulated including transport of oxygen, allowing accurate prediction of PEFC operation compared to experimental data.…”
Section: ■ Introductionmentioning
confidence: 99%